Immunometabolic Dysregulation at the Intersection of Obesity and COVID-19 - Khwatenge, Collins N.; Pate, Marquette; Miller, Laura C.; Sang, Yongming (Frontiers in Immunology, 2021)
Obesity prevails worldwide to affect increasingly, such as up to 42% of American adults. Obese individuals are prone to a variety of complications with metabolic disorders, including diabetes mellitus, hypertension, cardiovascular disease, and chronic kidney disease. Recent meta-analyses of clinical studies in patient cohorts of ongoing pandemic of coronavirus-disease 2019 (COVID-19), indicate that the presence of obesity and relevant disorders is linked to a severer prognosis of COVID-19. Given this significant coincidence of obesity in COVID-19 progression, we provide a review at the interface of host metabolic and immune responses by focusing on immunometabolic dysregulation that is exaggerated by obesity and the viral infection to develop into a severe course of COVID-19 syndrome. Moreover, sequela studies of individuals six months after having COVID-19 show that people who have been infected by the COVID-19 virus may have a higher risk to suffer metabolic comorbidities including obesity, diabetes, and kidney disease. These collectively implicate an inter-systemic dimension to understand the association between obesity and COVID-19, and suggest interdisciplinary intervention for relieving obesity-COVID-19 complication beyond the phase of acute infection.